Alternative polyadenylation: less than meets the eye? - Neve, J; Furger, A (Portland Press, 2014)
With the advances in deep-sequencing techniques over the last decade, the study of alternative cleavage and polyadenylation (APA) has shifted from individual gene to whole transcriptome analysis. Findings from such global studies have elevated APA to its currently accepted status as a major player in the regulation of eukaryotic gene expression. Although ~70% of human genes have been shown to contain multiple cleavage and polyadenylation sites, the extent of the consequences of APA and its role in regulating physiological processes are still largely unknown. The present review aims to summarize the experimental evidence that supports a physiological role of APA and highlights some of the shortcomings that need addressing to substantiate the widely proposed claim that APA is a key player in global gene regulation.